High intensity physical activities increase troponin I level but does not affect changing in glutathione peroxidase in mice - Moh Ali Ridho; Nining Widyah Kusnanik; Muhammad Ilham Mauluddin; Bambang Purwanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Muscle damage can be triggered by other free radicals formed during intense physical activites and the low response of antioxidants. The antioxidants that plays a role in responding to free radicals during physical activites is glutathione peroxidase.